Dynamic numerical simulation of different drill bit diameter on the polyurethane foams drilling - Fernandes, M.G.A. (2018)
Drilling is one of the most common processes involved in different cutting operations and may affect the mechanical properties of the workpiece by creating residual stresses around the opened hole and highly stressed on the newly formed surface.